The Influence of the Internet to Improve Students' Understanding of Arabic Vocabulary: A Semi-Experimental Study at Al-Mutahar Falyurid Islamic High School - Assyifa Nurzannah; Dede Rizal Munir; Ahmad Fajar; Taufik Luthfi (Solo Universal Journal of Islamic Education and Multiculturalism, 2023)
This research is motivated by the problems that occur in the process of teaching vocabulary for the tenth grade, which are the students' lack of understanding of teaching the Arabic language, the student's lack of interest in teaching the Arabic language, and the lack of student activity in teaching the Arabic language. This study aims to determine the effect of using the Internet on increasing students' understanding of Arabic vocabulary. The method used in this study is the use of quantitative methods with experimental study types and quasi-experimental designs. Data were collected in this study using observation, tests, and interviews. As for the results of this study, it was found that online media affected students' understanding of the study of vocabulary, which can be seen through an increase in the average score of students in the post-test, which reached 82.73. The regression test "F" value: is 10.777 with a value of 0.04 and the "T" test: is 3.283. with a value of 0.00. Therefore, it can be concluded that the Internet has an impact on teaching vocabulary to students